Essays in Education, Crime, and Job Displacement - Patrick Bennett (Copenhagen Business School (CBS), 2016)
With a limited budget and resources, governments must decide how to allocate funds across a variety of factors which benefit society such as education, crime deterrence, and public safety. Each increase in spending on one area comes with the knowledge that this money cannot be spent on social problems in another area. As such, externalities and unexpected spillover effects impact the costs and benefits of public spending to society and may have large and meaningful implications on how to most effectively allocate resources across a multitude of outcomes. For example, an increase in education corresponds to an increase in the opportunity cost of engaging in criminal activity, decreasing the probability an individual commits crime. Likewise, loss of employment decreases the opportunity cost of engaging in criminal activity, increasing the probability an individual commits crime. Discrimination towards immigrants can impact their employment prospects which, in turn, impacts their decision to further pursue education. Identifying how these individual level factors have an impact on society is key to informing and designing effective public policy. This Ph.D. thesis, entitled “Essays in Education, Crime, and Job Displacement”, analyzes the determinants and social implications of these three factors. While independent, each essay within this thesis examines the impact of factors such as education, in terms of reduced crime, job loss, in terms of increased crime, and discrimination, in terms of its impact on the educational attainment of immigrants, on society.
hdl:10398/9308
Keywords: 650